2004
DOI: 10.1021/ja048211h
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Formation of an Exfoliated Polystyrene−Clay Nanocomposite Using a Star-Shaped Polymer

Abstract: Mixtures of five-arm star polystyrene with an organoclay spontaneously formed exfoliated nanocomposites when annealed, validating a recent theoretical prediction by Singh and Balazs (Polym. Int. 2000, 49, 469.). An analogous linear polystyrene sample produced only an intercalated morphology under the same conditions. The nanocomposite morphologies were characterized by X-ray diffraction and transmission electron microscopy. These results suggest a general strategy for forming exfoliated nanocomposites in commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
56
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 8 publications
1
56
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] Fully exfoliated clay, however, is notoriously difficult to attain, particularly with non-polar polymers. Finding, understanding, and optimizing a simple and cost-effective method for preparing non-polar polymer-exfoliated-clay nanocomposites with high clay content remain significantly challenging.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Fully exfoliated clay, however, is notoriously difficult to attain, particularly with non-polar polymers. Finding, understanding, and optimizing a simple and cost-effective method for preparing non-polar polymer-exfoliated-clay nanocomposites with high clay content remain significantly challenging.…”
Section: Introductionmentioning
confidence: 99%
“…10 A great number of research has proven that the stronger interfacial bonding between the lamellae and matrix, and the homogeneous distribution of exfoliated lamella benefit higher mechanical strength. 1 To realize the exfoliation/delamination of layered silicates in com-posites, many strategies were submitted, such as organo-modification 11 and surface initiated polymerization 12 of layered silicates, polar group of polymer derivation 13 and compact polymer structure bearing multi polar groups (star, 14 dendritic, 15 and branched 16 structures).…”
Section: Introductionmentioning
confidence: 99%
“…Polymer-clay nanocomposites, as these materials are known, possess dramatically improved properties due to nanometre-sized dispersions of organically modified clay in the polymer matrix [8]. For example, incorporation of a few weight percent of clay in polymeric matrices brings appreciable increases in thermal and mechanical properties compared with their unmodified counterparts [9] and researchers at Toyota have demonstrated that nylon-6, following exfoliation with an inorganic filler possesses greatly improved thermal, mechanical, barrier, and even flame-retardant properties [10,11]. The general approach has since been extended to many other commercial polymers, including polyimides, polyamides, unsaturated polyesters, poly(oxyethylene), polystyrene, polystyrene maleic anhydride, amine-terminated butadiene acrylonitrile (ATBN), poly(methyl methyacrylate), polypropylene, poly(oligo(oxyethylene)) methacrylates, polyurethane and poly(butylene terephthalate) [12].…”
Section: Introductionmentioning
confidence: 99%